THE ROLE OF BANJAR ETHNIC PARENTS IN BUILDING CHARACTER IN CHILDREN THROUGH LOCAL EFFORT IN KOTA RANTANG VILLAGE, DELI SERDANG DISTRICT, NORTH SUMATRA - Abdi Syahrial Harahap; Hanipa Yansari (Proceeding International Seminar of Islamic Studies, 2023)
Banjar ethnicity comes from South Kalimantan. the Banjar ethnic population can also be found in the Riau, Jambi, North Sumatra regions. As with the ethnic Banjar in Rantang City, Hamparan Perak District. This study aims to determine the local wisdom of the Banjar ethnic in Kota Rantang Hamparan Perak Village, Deli Serdang Regency. In addition, this research will analyze the role of Banjar Ethnic Parents in Forming Character in Children Through local wisdom in Kota Rantang Hamparan Perak Village, Deli Serdang Regency. This research uses a qualitative method with a descriptive approach, while the object of research that we will examine is the Banjar ethnic community on the role of parents in shaping the character of children who are in Kota Rantang Village, Hamparan Perak District, Deli Serdang Regency. The results of this study indicate that 1) The results of the study indicate that there are several local wisdoms such as baayun mulud, Tula bala asba' mustakmir in shaping children's character education in Kota Rantang Village to form religious, honest, tolerant, disciplined and responsible characters in children through the baayun mulud tradition, 2) the role of parents is very decisive in the success of children in applying the values in the local wisdom of the Banjar ethnic in Kota Rantang Village.